Impact of public health education on the health status of the older migrant population - Yan, Zaohong; Han, Fang; Gao, Runguo; Jing, Qi; Gao, Qianqian; Cai, Weiqin (Frontiers in Public Health, 2022)
Background: Due to an increasing aging population, China has experienced a rapid expansion in its internal older migrant population who face greater health risks and who have a relatively high demand for health education. Public health education is an important means of preventing diseases and promoting health. However, many studies have focused on the utilization, with few studies examining the impact of public health education on the health of the older migrant population in China. Objectives: This study analyzed the impact of public health education on the health of the older migrant population in China. Methods: Based on data obtained from the National Migrant Population Health and Family Planning Dynamic Monitor Survey (2018), logistic models and propensity score matching were used to analyze the impact of public health education on the health of the older migrant population. Results: The self-assessed health of China’s older migrant population was good, and the acceptance rate of public health education was 40.81%. The public health status of the older migrant population receiving public health education significantly improved (p < 0.05). After correcting for endogeneity among the variables, public health education increased the probability of improving the older migrant population’s self-assessed health by 5.4% to 6.1% (p < 0.01). Heterogeneity analysis found that public health education had a greater impact on the health of older men with an education level of middle school and below, and especially on the older migrant population in the eastern region of China. Conclusions: Public health education positively affected the health status of the older migrant population. The characteristics and preferences of the older migrant population involving different genders, regions, and educational levels need to be considered, public health education needs to be standardized, and appropriate education methods need to be adopted that suit the older migrant population. Reference suggestions are provided for improving the health level of the older migrant population.